KONSEP KETATANEGARAAN PAKISTAN PERSPEKTIF FIQH SIYASAH - Muhammad Faqih; Ellyda Retpitasari (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
The purpose of this research is to find out the pakistani constitutional system in terms of tate institutions and fiqh siyasah. The method used is library reaserch with two approaches, namely conseptual approach and historical approach. The results of the research of the concept of Pakistani state regulation fiqh siyasah perspective in the era: (1) In general the state of Pakistan can be said to be a country with a weak democracies system, this is motivated by the unstable system of government and constitutional system since Pakistan's independence in 1947. In addition, the cause of the instability of the country is the violence and feud between three social forces, namely Hindus who are the majority in India, indian Muslims who are minorities and The British as invaders with modern political and technological forces that developed in the country of pakistan. (2) The establishment of the Indian Muslim League, Muhammad Ali Jinnah initiated the theory of